2004
DOI: 10.1038/sj.bjp.0705804
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of a bitter melon extract on the P‐glycoprotein activity in intestinal Caco‐2 cells

Abstract: 1 Extracts of bitter melon, soybean, dokudami and welsh onion by 40% methanol increased the accumulation of rhodamine-123 by Caco-2 cells, suggesting that these extracts inhibited Pglycoprotein (P-gp). 2 The extract of bitter melon was separated in a tC18 cartridge column and the eluate from 80% acetonitrile most markedly increased the [ 3 H]-daunomycin accumulation by Caco-2 cells. 3 The inhibitory compounds in the bitter melon fraction were isolated by HPLC with Pegasil C4 and Pegasil ODS columns. The HPLC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…Lipids, in particular monoglycerides, contained in a high-fat meal or its digests have been reported to inhibit P-glycoprotein transport. 14,15 Mirabegron has also previously been reported to have been adsorbed to food components, especially by components of low-fat meals. 8 In studies in healthy Chinese subjects, mirabegron C max was reached approximately 4 hours after oral administration of a single dose and approximately 5 hours after multiple-dose administration.…”
Section: Clinical Therapeutics 1040mentioning
confidence: 95%
“…Lipids, in particular monoglycerides, contained in a high-fat meal or its digests have been reported to inhibit P-glycoprotein transport. 14,15 Mirabegron has also previously been reported to have been adsorbed to food components, especially by components of low-fat meals. 8 In studies in healthy Chinese subjects, mirabegron C max was reached approximately 4 hours after oral administration of a single dose and approximately 5 hours after multiple-dose administration.…”
Section: Clinical Therapeutics 1040mentioning
confidence: 95%
“…Nanopore induction or the membrane perturbation (Anderson, 2005), and the intermediate phases formed in the intestine (Kossena et al, 2005) were considered important. In vitro study showed that monoglycerides can enhance the cellular absorption of drugs by inhibition of Pglycoproteins (Konishi et al, 2004). Further studies are required to explain the absorption enhancing mechanism of monoolein unequivocally.…”
Section: Discussionmentioning
confidence: 99%
“…48) Monopalmitate was observed to inhibit multi-drug resistance protein1 (MDR1 or P-glycoprotein), an efflux transporter for hydrophobic xenobiotics. 49) Although these lipid compounds are surface active, their surface activity did not correlate with the transport-inhibitory activity. Specific structures or characteristics of these compounds affect cell membrane structure or transporter structure itself, thereby regulating the activity of these membrane transporters.…”
Section: Modulation Of Transporter Functionsmentioning
confidence: 99%